Degraded landscapes as a tourist attraction and place for leisure and recreation - Chylińska, Dagmara; Kołodziejczyk, Krzysztof (Turyzm/Tourism, 2017)
The aim of the article is to assess the role of degraded landscapes in tourism. The authors try to answer questions about the contexts in which such landscapes may be found in relation to those complex phenomena concerning the human need for travel, leisure, cognition and experience. They also pose questions about the physical and symbolic limits to tourism and recreation in degraded landscapes. The work is based on a literature review and observations on chosen degraded landscapes (mostly industrial and post-industrial) located at the Czech foreground of the Ore Mountains (Czech Krušné Hory, German Erzgebirge).